Modern Shakespeare Offshoots - Cohn, Ruby (Book collections on Project MUSE., 1976)
Shakespeare's plays have never had a larger audience than they do in our time. This wide viewing is complemented by modern scholarship, which has verified and elucidated the plays' texts. Nevertheless, Shakespeare's plays continue to be revised. In order to find out how and why he has been rewritten, Ruby Cohn examines modern dramatic offshoots in English, French, and German. Surveying drama intended for the serious theater, the author discusses modern versions of Shakespeare's plays, especially Macbeth, Hamlet, King Lear, and The Tempest. Although the focus is always on drama, contrast is s.